(x+8i)(2x-9i)=

Simple and best practice solution for (x+8i)(2x-9i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8i)(2x-9i)= equation:


Simplifying
(x + 8i)(2x + -9i) = 0

Reorder the terms:
(8i + x)(2x + -9i) = 0

Reorder the terms:
(8i + x)(-9i + 2x) = 0

Multiply (8i + x) * (-9i + 2x)
(8i * (-9i + 2x) + x(-9i + 2x)) = 0
((-9i * 8i + 2x * 8i) + x(-9i + 2x)) = 0

Reorder the terms:
((16ix + -72i2) + x(-9i + 2x)) = 0
((16ix + -72i2) + x(-9i + 2x)) = 0
(16ix + -72i2 + (-9i * x + 2x * x)) = 0
(16ix + -72i2 + (-9ix + 2x2)) = 0

Reorder the terms:
(16ix + -9ix + -72i2 + 2x2) = 0

Combine like terms: 16ix + -9ix = 7ix
(7ix + -72i2 + 2x2) = 0

Solving
7ix + -72i2 + 2x2 = 0

Solving for variable 'i'.

Factor a trinomial.
(-8i + -1x)(9i + -2x) = 0

Subproblem 1

Set the factor '(-8i + -1x)' equal to zero and attempt to solve: Simplifying -8i + -1x = 0 Solving -8i + -1x = 0 Move all terms containing i to the left, all other terms to the right. Add 'x' to each side of the equation. -8i + -1x + x = 0 + x Combine like terms: -1x + x = 0 -8i + 0 = 0 + x -8i = 0 + x Remove the zero: -8i = x Divide each side by '-8'. i = -0.125x Simplifying i = -0.125x

Subproblem 2

Set the factor '(9i + -2x)' equal to zero and attempt to solve: Simplifying 9i + -2x = 0 Solving 9i + -2x = 0 Move all terms containing i to the left, all other terms to the right. Add '2x' to each side of the equation. 9i + -2x + 2x = 0 + 2x Combine like terms: -2x + 2x = 0 9i + 0 = 0 + 2x 9i = 0 + 2x Remove the zero: 9i = 2x Divide each side by '9'. i = 0.2222222222x Simplifying i = 0.2222222222x

Solution

i = {-0.125x, 0.2222222222x}

See similar equations:

| 1200/30.24=1200*r/1 | | y=3x*2+2x-8 | | 16x^2+(-24x)-16=0 | | 90p^2+114p-48=0 | | 1200*r/30.24 | | 13+3n-7n+1=-14n+9n | | (65)65+(65)65= | | -(-3y+v)+3(5v-6y)= | | (4x)(2w^8)(6x^4w^3)= | | -4y+11=17-3y | | 15b/2a | | 2w+4x+15y+6w+11x+7y= | | 4ab/5b^4 | | x^2=0.0016 | | 3+3.2p=5.56 | | 1*(-4+(-8))= | | 3.2p=5.56 | | 7/x=2 | | X^2=4900 | | 30=5(x+11) | | 4.3-1.95x=4.4-1.98x | | x/7=0.02 | | g(x)=-2x^2-3 | | 123=7 | | (4x-8)+2=12 | | 30/8=90/m | | 3s-21=-12+2s | | 7y-2=-56+y | | 75n+100=5509 | | x/7=0.18 | | 5/3s=10 | | -5/9m=-20 |

Equations solver categories